Inflammatory Factors of Macular Atrophy in Eyes With Neovascular Age-Related Macular Degeneration Treated With Aflibercept - Sato, Tomohito; Enoki, Toshio; Karasawa, Yoko; Someya, Hideaki; Taguchi, Manzo; Harimoto, Kozo; Takayama, Kei; Kanda, Takayuki; Ito, Masataka; Takeuchi, Masaru (Frontiers in Immunology, 2021)
Background. Neovascular age-related macular degeneration (nAMD) is a leading cause of blindness in older people. Low-grade inflammation is well-known as one of pathogenic mechanisms in nAMD. Anti-vascular endothelial growth factor (VEGF) therapy is the first-line treatment for nAMD, although macula atrophy (MA) developed under anti-VEGF therapy causes irreversible visual function impairment, and is recognized as a serious disorder. Here we show specific expression patterns of aqueous humor (AH) cytokines in nAMD eyes developing MA under intravitreal injection of aflibercept (IVA) as an anti-VEGF antibody, and present predictive cytokines as biomarker for incidence of MA in nAMD eyes under IVA treatment. Methods. Twenty-eight nAMD patients received 3 consecutive monthly IVA, followed by a pro re nata regimen for 2 years. AH specimens were collected before first IVA (pre-IVA) and before third IVA (post-IVA). AH cytokine levels, visual acuity (VA) and central retinal thickness (CRT) were measured. Results. Two-year incidence of MA was 21.4%. In nAMD eyes developing MA [MA (+) group], pre-IVA levels of monocyte chemoattractant protein-1 (MCP-1), macrophage inflammatory protein (MIP)-1β, VEGF, and post-IVA level of MCP-1 were higher than those in nAMD eyes without MA [MA (−) group]. In hierarchical cluster analysis, pre-IVA MCP-1 and VEGF were grouped into the same subcluster, as were post-IVA MCP-1 and CRT. In principal component analysis, principal component loading (PCL) of pre-IVA interferon-γ inducible protein 10 (IP-10) was 0.61, but PCL of post-IVA IP-10 decreased to −0.09. In receiver operating characteristic analysis and Kaplan-Meier curves, pre-IVA MCP-1, MIP-1β, VEGF, and post-IVA interleukin-6, MCP-1, MIP-1β were detected as predictive factors for MA incidence. In 2-year clinical course, changes of VA in groups with high levels of pre-IVA MIP-1β (over 39.9 pg/mL) and VEGF (over 150.4 pg/mL) were comparable to those in MA (+) group. Conclusion. Substantial loss of IP-10 effects and persistent inflammation contribute to incidence of MA, and screening of AH cytokine levels could be a useful method to predict MA incidence in nAMD eyes under anti-VEGF therapy.